Uji Sifat Fisik dan Mikrobiologi Sediaan Lulur Krim yang Mengandung Serbuk Kopi serta Penentuan Aktivitas Antioksidannya - Warditiani, Ni Kadek (Jurnal Farmasi Udayana; Vol. 12, No 1, Tahun 2023DO - 10.24843/JFU.2023.v12.i01.p11, 2023)
In 2017 the Ministry of Industry noted Indonesia’s cosmetics industry in the country out numbered to 760 companies. Further, 95% of the industry is dominated by small to medium industrial sector, for this reason, in order to comply with international standards and certification bodies, it is necessary to guarantee the product quality. One of the product tested was a cream scrub containing coffee. Coffee has various chemical compounds that have antioxidant activity which plays a very important role in preventing premature aging. The product quality testing carried out is physical testing, microbiology and also the determination of antioxidant activity. From the prior tests , it was found that the pH of the preparation was 5.73 for the type of oil-in-water emulsion, the spreadability was 5.34 and 6.29 cm. Adhesion 11.10 seconds. The preparation meets all microbiological requirements and has an IC50% of 69.09 ppm.